The Effective Way of Solving Problems of the Elementary School Pupils’ Learning Difficulties - Widodo, Slamet; Ardhyantama, Vit (Journal of Islam and Science, 2020)
The competence of the elementary school teacher candidates to solve the problem of the pupil's learning difficulties is essential, since in the school the teacher will solve the problems by himself. Therefore, direct practice is required for students to solve problems of learning difficulties. The purpose of this study is to describe the various ways that the students choose to solve the problem of the learning difficulties of elementary school pupils. The design of this study uses a qualitative descriptive approach through techniques of data collection in the form of observation, interview and questionnaire, while data analysis techniques use interactive analysis techniques. The results of this study indicate that the students' ability increases in solving learning difficulties of elementary pupils. In one hand, each student has an effective and unique way to solve the problem: improve the quality of oneself through prayer and learning, solve problems through a scientific approach and evaluate correcting mistakes and improving for better results.